Characterizing subtypes and neural correlates of receptive aprosodia in acute right hemisphere stroke. (August 2021) - Sheppard, Shannon M.; Meier, Erin L.; Zezinka Durfee, Alexandra; Walker, Alex; Shea, Jennifer; Hillis, Argye E.
Abstract: Introduction: Speakers naturally produce prosodic variations depending on their emotional state. Receptive prosody has several processing stages. We aimed to conduct lesion-symptom mapping to determine whether damage (core infarct or hypoperfusion) to specific brain areas was associated with receptive aprosodia or with impairment at different processing stages in individuals with acute right hemisphere stroke. We also aimed to determine whether different subtypes of receptive aprosodia exist that are characterized by distinctive behavioral performance patterns. Methods: Twenty patients with receptive aprosodia following right hemisphere ischemic stroke were enrolled within five days of stroke; clinical imaging was acquired. Participants completed tests of receptive emotional prosody, and tests of each stage of prosodic processing (Stage 1: acoustic analysis; Stage 2: analyzing abstract representations of acoustic characteristics that convey emotion; Stage 3: semantic processing). Emotional facial recognition was also assessed. LASSO regression was used to identify predictors of performance on each behavioral task. Predictors entered into each model included 14 right hemisphere regions, hypoperfusion in four vascular territories as measured using FLAIR hyperintense vessel ratings, lesion volume, age, and education. A k -medoid cluster analysis was used to identify different subtypes of receptive aprosodia based on performance on the behavioral tasks. Results: Impaired receptive emotional prosody and impaired emotional facial expression recognition were both predicted by greater percent damage to the caudate. The k- medoid cluster analysis identified three different subtypes of aprosodia. One group was primarily impaired on Stage 1 processing and primarily had frontotemporal lesions. The second group had a domain-general emotion recognition impairment and maximal lesion overlap in subcortical areas. Finally, the third group was characterized by a Stage 2 processing deficit and had lesion overlap in posterior regions. Conclusions: Subcortical structures, particularly the caudate, play an important role in emotional prosody comprehension. Receptive aprosodia can result from impairments at different processing stages.